The Reality of Legitimacy Alternatives of financial Derivatives in the Light of the Islamic Financial Engineering Products - ATROUS, SABRINA (Milev Journal of Research and Studies, 2015)
Financial Derivatives are regards as the most important products of financial engineering and the most important financial inventions and innovations reached by the centers of research and development. Derivatives are financial instruments its value linked with certain financial tool or any index or good which help to buy and sell financial risks in the financial markets. The option contracts, future contracts, future and swap contracts are the most important types of financial derivatives and the most current traded in the financial markets. But the dealing by these tools in terms of legitimacy is not permissible because they contradict mildly with the Sharia, and they involve suspicious transactions of bribery and gambling. However, there are legitimate alternatives, which are proved to be efficient, and which can replace these derivatives, like contract of peace, the rent contract, the deferred sale, and option condition.